Civil status regarding entry into the clergy - Mohor-Obreja, Bogdan (Technium Social Sciences Journal, 2023)
For the Orthodox Church, the priesthood is the cornerstone of its role and what it means. From a functional point of view, the priesthood is an accumulation of duties and rights that are specific and found only within the Church, including the legitimacy of the exercise of these duties and rights.